2020
DOI: 10.21203/rs.3.rs-54212/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

miR-361-3p Regulates Liver Tumor-initiating Cells Expansion and Chemo-resistance

Abstract: Background: Increasing evidence shows that liver tumor-initiating cells (T-ICs) closely associated with the progression, metastasis, recurrence and chemo-resistance of hepatocellular carcinoma (HCC). However, the underlying mechanism for the propagation of liver T-ICs remains unclear. The purpose of our study was to explore the role of miR-361-3p in the expansion of liver T-ICs and the potential molecular mechanism.Results: Flow cytometry analysis was performed to isolate CD24+, CD133+ or EpCAM+ cells from pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…MiR-361-3p expression is upregulated in HCC cells and liver tumorinitiating cells. The dysregulated expression of miR-361-3p enhances the self-renewal and tumorigenic liver tumor-initiating cells [25,26]. In agreement with findings from previous studies, we also observed a decrease in miR-361-3p expression in HCC tissues and cell lines.…”
Section: Discussionsupporting
confidence: 92%
“…MiR-361-3p expression is upregulated in HCC cells and liver tumorinitiating cells. The dysregulated expression of miR-361-3p enhances the self-renewal and tumorigenic liver tumor-initiating cells [25,26]. In agreement with findings from previous studies, we also observed a decrease in miR-361-3p expression in HCC tissues and cell lines.…”
Section: Discussionsupporting
confidence: 92%
“…Compared with control cells, overexpression of miR-361-3p in HCC induced greater tumorigenicity and lower sensitivity to cisplatin through a mechanism that involves SOX1 binding. In addition, high levels of miR-361-3p in HCC patients treated with postoperative TACE were associated with shorter survival, 52 suggesting that this miRNA could be used as a prognostic biomarker.…”
Section: Mechanisms Of Pharmacoresistancementioning
confidence: 99%
“…32 miR-361-3p has been rstly demonstrated as a novel oncogene. 23 Additional works continue to elucidate that miR-361-3p regulates the proliferation, migration, and invasion of human liver cancer, 33 prostate cancer cells, 21 and oral squamous cell carcinoma (OSCC). 20 For instance, miR-361-3p induced cell proliferation and promoted EMT through negative regulation of dual speci city phosphatase-2 (DUSP2), thereby activating ERK signaling in pancreatic cancer cells.…”
Section: Discussionmentioning
confidence: 99%